Paracriodion Fragoso (Coleoptera: Cerambycidae: Cerambycinae): redefinition, with description of a new species from Bolivia - Monné, Miguel A. (Zootaxa, 2014)
The genus Paracriodion Fragoso, 1982, is redefined. A new species from Bolivia, P. morrisi sp. nov., is described. A key for Paracriodion species is included and new distributional data for P. romani (Aurivillius, 1926) are given.